Description of Macrobiotus kathyae sp. nov. (Parachela: Macrobiotidae) and first records of tardigrades from Indiana (USA) - Massa, Edoardo; Vecchi, Matteo (Zootaxa, 2024)
The integrative description of the new species Macrobiotus kathyae sp. nov. is reported in this study along with the first tardigrade records for Indiana (United States of America). The new species is characterized by having spines in the distal part of the processes ornamenting the free laid eggs. This modified Macrobiotus-type of ornamentations was previously reported also in Macrobiotus annewintersae Vecchi & Stec, 2021 with which the new species forms a monophyletic clade. In seven out of the nine examined samples, eight tardigrade taxa were found including the new species, the first record outside the type locality of Macrobiotus basiatus Nelson et al., 2020, and the northernmost location for the genus Barbaria.